A4.4 Circulating Metastasis Promoting Protein S100A4 in Idiopathic Inflammatory Myopathies. (25th February 2013) - Pleštilová, L; Pecha, O; Mann, H; Cerezo, LA; Vencovský, J; Šenolt, L
Abstract : Background and Objectives: Metastasis promoting protein S100A4 is involved in the pathogenesis of tumours and chronic autoimmune diseases such as rheumatoid arthritis (RA) and psoriasis. We recently described increased expression of S100A4 in inflamed muscle tissue in patients with idiopathic inflammatory myopathies (IIM). Since circulating levels of S100A4 correlate with disease severity in RA patients, we therefore evaluated the association between S100A4 protein and disease activity in patients with IIM and compared S100A4 serum levels in myositis patients and healthy controls in this study. Methods: Serum levels of S100A4 protein were determined in 43 dermatomyositis (DM), 39 polymyositis (PM) and 22 cancer associated myositis (CAM) patients and in 89 healthy controls. In 11 patients (4 DM, 3 PM, 4 CAM), S100A4 serum levels were measured before and after the start of treatment. The associations between S100A4 levels, inflammation, disease activity and muscle strength were examined. Disease activity was assessed using Disease Activity Core Set Measures developed by International Myositis Assessment & Clinical Studies Group (IMACS). Serum levels of C-reactive protein (CRP) and muscle-associated enzymes creatine phosphokinase (CK) and lactate dehydrogenase (LD) were measured by routine laboratory methods. Results: In patients with PM, serum levels of S100A4 protein were significantly higher than those observed in healthy controls or DM patients (148.6 ± 351.5 versus 80.75 ± 285.1, p < 0.01 and 43.55 ± 53.03, p < 0.05, respectively). No significant differences in S100A4 levels were found between CAM patients (119.9 ± 414.0) and healthy controls or other myositis patients. In the whole group of IIM patients, serum S100A4 levels correlated with MYOACT score (r = 0.39; p < 0.001) and its components Constitutional Disease Activity (DA) (r = 0.34; p < 0.001) and Pulmonary DA (r = 0.44; p < 0.001). Serum S100A4 correlated also with Muscular DA (r = 0.25; p < 0.05), CK (r = 0.33; p < 0.01) and LD (r = 0.40; p < 0.001). S100A4 levels correlated with Cutaneous DA (r = 0.46; p < 0.01) in DM patients and with Extramuscular Global Assessment only in PM patients (r = 0.55; p < 0.001). No significant correlations of S100A4 serum levels in patients with CAM were found. In the 11 longitudinal IIM samples there was no significant decrease of S100A4 serum levels observed. Multiple regression of the whole IIM patients group showed significant association of S100A4 serum levels with Pulmonary DA (β = 0.369; p < 0.01), LD (β = 0.345; p < 0.01) and severity of dysphagia (β = –0.250; p < 0.05). In PM patients, S100A4 levels were associated with Extramuscular Global Assessment (β = 0.552; p < 0.01) and in DM patients with MYOACT (β = 0.557; p < 0.01) and CRP (β = 0.391; p < 0.05). Conclusions: This is the first study showing that circulating levels of S100A4 are associated with several features of IIM disease activity, particularly with extramuscular components. We did not find any association of S100A4 levels and cancer associated myositis. Further studies analysing bioactive form of S100A4 and the role of S100A4 in cancer associated myositis are needed.